Human Resource Development and Employee Engagement in Nepalese Commercial Banks - Hakuduwal, Kishor (Journal of Business and Social Sciences Research, 2019)
The objective of the present study is to analyse the impact of human resource development on employee engagement in Nepalese commercial banks by taking three human resource development components of training and development, career development and performance management as independent variables, and employee engagement as a dependent variable. Using the random sampling, 384 employees were selected, and a questionnaire survey was carried out to collect data. Using F-test and t-test, the study found that the training and development, career development and performance management have significant impact on employee engagement in Nepalese commercial banks. The study also revealed that male employees have more emphasis on performance management but female employees have more emphasis on training and development. Likewise, the employees up to the officer level have also more emphasis on performance management but the employees below officer level have more emphasis on training and development.